Study on precursory characteristics of granite failure based on infrasonic energy - Jian-ping Wei; Bing Jia; Zhi-hui Wen; Lin-xing Jia (Results in Physics, 2017)
To study signal characteristics of precursory infrasound of granite failure, coal-rock stress loading device and infrasound acquisition device were adopted to perform infrasound test in uniaxial loading process for granite samples. Wavelet filtering, infrasonic energy methods were used to process and analyze the test results. The results show that the infrasonic waves caused by the failure of rock samples are mainly in the middle and low frequency. Moreover, in the loading process, the ratio of relative energy of infrasound in different frequency sections and the total relative energy of the whole low frequency section both exhibit significant regularity of stage change, which is in consistent with the compaction stage, elastic stage, plastic stage of rock deformation. Additionally, the precursory characteristics of infrasound before rock failures are prominent and easy to be recognized. Meanwhile, infrasonic wave has the advantage of low attenuation in propagation process, which grants the superiority of infrasound prediction technology. A new method of rock failure prediction based on infrasound is formed, which provides an important reference for rock damage prediction in coal mining process. Keywords: Infrasonic energy, Wavelet filtering, Precursory characteristics, Failure prediction